Religiosity and misuse of school aid funds: The development of the fraud theory - Abdul Rohman; Hasan Mukhibad; Ahmad Nurkhin (Institute of Advanced Engineering and Science, 2023)
Fraud is a problem that occurs in various organizations, including educational institutions. This condition is very ironic, educational institutions as institutions are required to teach anti-fraud education, but in fact, the educational institutions themselves are still fraudulent. This study aimed to explain the factors that can influence the principal, treasurer, and school committee to abuse school aid funds. The research sample was 145 principals, treasurers, and school committees for the elementary, junior high, and senior high school levels selected by convenience sampling method. All variables were measured using five Likert scales and analyzed with the multiple regression method. Instrument validity test using Pearson product-moment. This study shows that we found that pressure, internal control, integrity, and religiosity influence fraud. High financial pressures stemming from greed, a luxurious lifestyle, debt, integrity, low systems of control, and religiosity can increase fraud. These results reinforce the importance of schools or education-related regulatory agencies to be able to take policies to form a school environment that encourages honesty, limits teachers to hedonism, has a fair compensation system, and encourages teachers to practice worship, which needs to be done to avoid financial fraud from abuse of school aid funds.